To Bear or Not to Bear: Personal and Familial Correlates of Parenthood Desires Among Filipino Adolescents - Rodenas, Mark Joseph P. (Animo Repository, 2023)
Having children in the future is a crucial decision backed by reason and shaped by experience and perceptions beginning from childhood. In the adolescent stage, one already has notions about whether he or she wants to have children. Although without certainty, the desires formed during adolescence are influential and reflective of future fertility plans in adulthood. Therefore, these desires and the factors affecting them must be clearly understood. However, not much is known about these factors. Using a cross-sectional survey design, this study sought to determine the parenthood desires of adolescent senior high school students from a private university in Manila and its relationship with personal factors and familial factors. Results reveal that a majority of adolescents (64.7%) want to have children. Overall, males expressed a stronger desire than females. Regarding their desires, adolescents wish to have their first child at 28.73 years old. They want an average of 2.41 children, spaced 2.53 years apart. Among those who want children, the most significant correlates of the desired number of children are the quality of maternal relationships (R2 = .067, F [1, 197] = 14.13, p = <.001), sibship size (R2 = .52, F [1, 196] = 11.57, p = <.001) and sex (R2 = .021, F [1, 195] = 4.85, p = <.029).